Evidence that the packaging signal of Moloney murine leukemia virus extends into the gag region. - Bender, M A (1987)
Replication-competent retroviruses can be modified to carry nonviral genes. Such gene transfer vectors help define regions of the retroviral genome that are required in cis for retroviral replication. Moloney murine leukemia virus has been used extensively in vector construction, and all of the internal protein-encoding regions can be removed and replaced with other genes while still allowing production of virions containing and transmitting the altered retroviral genome. However, inclusion of a portion of the gag region from Moloney murine leukemia virus markedly increases the titer of virus derived from these vectors. We determined that this effect was due to more efficient packaging of the vector RNA into particles and did not depend on protein synthesis from the gag region. We conclude that the retrovirus packaging signal extends into the gag region. We have found that retroviral vectors containing the complete packaging signal allow more efficient gene transfer into a variety of cell types. In addition, these results may help explain why many oncogenic retroviruses have retained gag sequences and often express transforming proteins that are gag-onc hybrids.